Association of Vaginal Microbiome Dysbiosis and Serum C-Reactive Protein with the Severity of Gestational Diabetes Mellitus: A Prospective Observational Study - Dr. Varshaa Krishna, Dr. Nidhi Sharma (Journal of Daoist Studies, 2026)
Background Gestational diabetes mellitus (GDM) is a common metabolic disorder of pregnancy and is associated with increased maternal and neonatal complications. Recent studies suggest that alterations in the vaginal microbiome and chronic low-grade inflammation may contribute to worsening glucose intolerance during pregnancy. However, evidence evaluating the relationship between vaginal microbiome dysbiosis, systemic inflammation, and the severity of GDM remains limited, particularly in the Indian population. We planned this study to assess the association between vaginal microbiome dysbiosis, serum high-sensitivity C-reactive protein (hs-CRP), and disease severity in women with GDM. Methods This prospective observational study was conducted in the Department of Obstetrics and Gynaecology at Saveetha Medical College and Hospitals, Chennai. Eighty pregnant women diagnosed with GDM according to the International Association of Diabetes and Pregnancy Study Groups (IADPSG) criteria were enrolled. Vaginal microbiome status was assessed using Nugent scoring on Gram-stained vaginal smears. Serum CRP levels, fasting plasma glucose, and glycated haemoglobin (HbA1c) were measured at enrolment. GDM was classified into mild, moderate, and severe categories. Statistical analysis included Chi-square test, one-way ANOVA, Spearman correlation, and multivariable logistic regression. Results Among the 80 women included in the study, 27 (33.8%) had mild GDM, 32 (40.0%) had moderate GDM, and 21 (26.2%) had severe GDM. Vaginal dysbiosis (Nugent score ≥7) was identified in 38.8% of participants and increased progressively with disease severity, from 11% in mild GDM to 47% in severe GDM (p <0.001). Mean serum CRP levels also increased significantly across vaginal microbiome categories, measuring 4.2 ± 1.1 mg/L in women with normal vaginal flora, 8.7 ± 1.8 mg/L in those with intermediate flora, and 15.3 ± 2.4 mg/L in women with vaginal dysbiosis (p <0.001). A strong positive correlation was observed between Nugent score and serum CRP levels (ρ = 0.74, p <0.001). Women with vaginal dysbiosis also had significantly higher rates of preterm birth, neonatal intensive care unit admission, postpartum infection, and macrosomia. On multivariable logistic regression analysis, vaginal dysbiosis and elevated hs-CRP remained independent predictors of severe GDM. Conclusion Vaginal microbiome dysbiosis is common among women with gestational diabetes mellitus and is significantly associated with increased systemic inflammation and greater disease severity. Simple and widely available investigations such as Nugent scoring and serum CRP estimation may help identify women at increased risk of severe GDM and adverse pregnancy outcomes. Larger multicentre studies using molecular microbiome analysis are needed to validate these findings and to evaluate the role of microbiome-based interventions in improving maternal and neonatal outcomes.